87.8k views
0 votes
Question is in the image

Question is in the image-example-1
User Kenneth Li
by
5.2k points

2 Answers

4 votes

Answer:

y=(-2/3)x^2

Step-by-step explanation:

User Sarath Chandra
by
5.6k points
4 votes

Answer: g(x) = (-2/3)x^2

=====================================================

Step-by-step explanation:

The blue parent function has a positive coefficient of 1. The purple g(x) function is a reflection of f(x) over the x axis, so everything is now negative. The coefficient must be negative as well.

But the answer is simply not g(x) = -x^2 because plugging x = 3 does not lead to y = -6 as the point (3,-6) shows.

Let's say the coefficient is k for now. So we have y = kx^2

Plug in x = 3 and y = -6. Solve for k

y = kx^2

-6 = k(3)^2

-6 = k*9

9k = -6

k = -6/9

k = -2/3

So we update y = kx^2 into y = (-2/3)x^2

Meaning that g(x) = (-2/3)x^2 is the equation of the purple curve.

Plug x = 3 into g(x) to find that

g(x) = (-2/3)x^2

g(3) = (-2/3)(3)^2

g(3) = (-2/3)(9)

g(3) = -6

which is the output we want, so this confirms we have the correct coefficient.

User Mmw
by
5.7k points